Real-World Treatment Patterns, Survival, and Costs for Ovarian Cancer in Canada: A Retrospective Cohort Study Using Provincial Administrative Data - Manjusha Hurry; Shazia Hassan; Soo Jin Seung; Ryan N. Walton; Ashlie Elnoursi; Jacob D. McGee (Journal of Health Economics and Outcomes Research)
# Background In 2020, approximately 3100 Canadian women were diagnosed with ovarian cancer (OC), with 1950 women dying of this disease. Prognosis for OC remains poor, with 70% to 75% of cases diagnosed at an advanced stage and an overall 5-year survival of 46%. Current standard of care in Canada involves a combination of cytoreductive surgery and platinum-based chemotherapy.